2018
DOI: 10.1155/2018/4183203
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Meteorological and Air Pollution Parameters with Pneumonia in Elderly Patients

Abstract: Background and Purpose In this study, we aimed to evaluate the relationship between pneumonia and meteorological parameters (temperature, humidity, precipitation, airborne particles, sulfur dioxide (SO2), carbon monoxide (CO), nitrogen dioxide (NO2), nitrite oxide (NO), and nitric oxide (NOX)) in patients with the diagnosis of pneumonia in the emergency department. Methods Our study was performed retrospectively with patients over 65 years of age who were diagnosed with pneumonia. The meteorological variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 43 publications
5
20
1
5
Order By: Relevance
“…Unsafe drinking water and sanitation are important drivers of pneumonia 47 . Relative humidity was associated with a decrease in pneumonia incidence in this study which is in concordance with other studies 35,48 . Higher relative humidity decreases the survival of lipid-enveloped viruses such as influenza A, influenza b and Respiratory Syncytial Virus 49,50 .…”
Section: Discussionsupporting
confidence: 93%
“…Unsafe drinking water and sanitation are important drivers of pneumonia 47 . Relative humidity was associated with a decrease in pneumonia incidence in this study which is in concordance with other studies 35,48 . Higher relative humidity decreases the survival of lipid-enveloped viruses such as influenza A, influenza b and Respiratory Syncytial Virus 49,50 .…”
Section: Discussionsupporting
confidence: 93%
“…After removing 835 studies during title and abstract screening, 103 were selected for full-text review, and 82 studies were excluded for the following reasons: reviews or letter (n = 4), different outcomes (n = 3), combined outcomes (n = 31), irrelevant studies (n = 10), not providing short-term effects (n = 3), not providing overall effects (n = 10), conducted in children (n = 1), unable to extract data (n = 1), and overlapping studies (n = 19). Finally, 21 studies were included for meta-analysis [9,10,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, published reports have shown that meteorological factors such as temperature and barometric pressure, have a negative influence on respiratory diseases[10,11]. A study conducted in Hong Kong demonstrated that per 1°C increase in wintertime was associated with 1.20% (95% CI, 1.08–1.32) increase for total respiratory diseases hospitalization and 1.41% (95% CI, 1.15–1.71) increase for COPD hospitalization[12].…”
Section: Introductionmentioning
confidence: 99%